CAKUPAN PELAYANAN KESEHATAN IBU DAN ANAK PADA MASA PANDEMIC COVID 19 DI PUSKESMAS MANDALA - Rokayah, Yayah; Kuswandi, Kadar (Jurnal Medikes (Media Informasi Kesehatan), 2023)
Health services during a pandemic are a problem for the community and the health workers. Providing services during this period is very risky to public health, especially for pregnant women, babies, and toddlers. The lack of public knowledge about the spread and prevention of COVID-19 will affect the attitudes and behavior of the community (pregnant women, maternity, infants, and toddlers) to visit healthcare centers out of fear. The study aimed to determine the difference in the average coverage of the Mother and Child Health Program before and after the Covid 19 pandemic. The research design used a cross-sectional sample. This study sample resulted from the coverage of MCH health services (ANC, childbirth, and neonatal) from January to September 2020. This research was conducted at the Mandala Health Center. Data collection used secondary data from the PWS report register. The results obtained mean coverage of all variables (ANC of 1.492%, Linakes of 1.78%, and Neonates of 3.698%) experienced an increase after the spread of the Covid-19 pandemic when compared to the average before the spread of the Covid-19 pandemic. The highest mean coverage was neonatal services at 3.698%. At the same time, the results of the T-test showed that the p values obtained for all variables were (ANC P value of 0.243, Linakes P value of 0.082, and Neonates P value of 0.091) exceeding the alpha value used (0.05), thus in this T-Test, it was found that the average coverage before and after the spread of information about Covid-19 did not experience a significant difference. There was an increase in the average coverage and MCH (ANC, delivery by health workers and neonates) after the COVID-19 pandemic, and there was no significant impact from the COVID-19 pandemic on the coverage of the MCH program.